Implementation of 2013 Curriculum in Teaching English at Rural Areas Junior High Schools in Luwu Utara Regency - Nita S; Andi Tenri Ampa; Erwin Akib (Journal of Development Research, 2022)
The aims of this research were: (1) to find out how teachers in rural areas implement the 2013 curriculum in teaching English (2) to find out what problems are faced by English teachers in rural areas in implementing the 2013 curriculum. This research used a qualitative method. The subjects of this research were English teachers of SMPN 9 Seko, SMPN 1 Seko, and SMPN 2 Seko. The total number of subjects was five English teachers. The procedure of this research was collected by doing observation and interviewing the English teachers using questionnaires. The results of this research showed that: first, implementation of the 2013 curriculum in Seko District as a rural area is still not going well and ineffective because there are still components of the teaching and learning process that have not been implemented systematically and precisely in the teaching and learning process. Second, the result based on the interview was the first problem that the teachers faced in teaching English in rural areas is the unavailability of learning media and most of the students still used their local language or mother tongue as a daily language which makes students usually do not understand well when teachers explain the lesson.